The Faces of Joke Parties: Comparative Analysis of the Party Organization of the Hungarian Two-tailed Dog Party and the Die PARTEI - Szegedi Peter (Politics in Central Europe)
This research aims to examine the organisational structure of two so-called joke parties: the Hungarian Two-Tailed Dog Party (MKKP) and the German Die PARTEI. These parties occupy a unique position within their respective party systems, as neither has secured seats in the national parliament. However, both have achieved notable successes in secondary elections, such as the European Parliament elections and at the local level. Despite being primarily recognised for their humorous, satirical and ironic communication strategies, this study seeks to move beyond the surface level of their political messaging and explore their deeper organisational structures. It is hypothesised that joke parties, as a distinct party family, share structural similarities beyond their communication style. To investigate this, two key theories of party organisation have been applied. The first is the ‘three faces’ theory proposed by Peter Mair and Peter Katz, which challenges the notion of monolithic party organisation and instead conceptualises parties as entities composed of separate yet interconnected segments, each with distinct functions, powers and responsibilities. The second theoretical framework is the movement party theory, which suggests that the boundaries between political parties and social movements are less rigid than traditionally assumed in political science. This theory posits that certain parties maintain stronger ties with civil society, exhibit grassroots organisational structures, emphasise direct democracy and prioritise street -level activism. To test this hypothesis, semi -structured interviews were conducted with members of Die PARTEI and MKKP. A diverse range of respondents was selected to ensure comprehensive data collection across national, regional (state), and local levels. In addition to analysing the vertical structure of these parties, their horizontal organisation was also examined. Consequently, data were gathered from prominent figures representing the party on the ground, the party in public office and the party in the central office. The findings indicate that both parties exhibit common organisational characteristics. Notably, the segment referred to as the ‘party on the ground’ appears to be the most prominent, as their political activity places significant emphasis on street -level engagement. Furthermore, both parties demonstrate stronger connections with civil society than traditional cartel parties, aligning them with the characteristics of movement parties.